Hydroxytyrosol exerts an anti-inflammatory effect by suppressing Toll-like receptor 2 and TLR 2 downstream pathways in Staphylococcus aureus-induced mastitis in mice. (August 2017) - Wu, Haichong; Jiang, Kangfeng; Zhang, Tao; Zhao, Gan; Deng, Ganzhen
Highlights: Hydroxytyrosol is an effective compound extracted from virgin olive oil. Hydroxytyrosol dose-dependently inhibited the expression of IL-1β, IL-6, and TNF-α. Hydroxytyrosol inhibited TLR2-mediated NF-κB and MAPK pathways activation. Hydroxytyrosol had a protective effect on S. aureus -induced inflammation. Abstract: Hydroxytyrosol (HT), a compound extracted from virgin olive oil, has been reported to exert anti-inflammatory activity. This study was aimed to evaluate the effects of HT on Staphylococcus aureus ( S. aureus) -induced inflammatory responses and explore the potential mechanism involved. HT administration was applied in both a mouse model and mouse mammary epithelial cells (MMECs). In vivo study, the results showed that HT attenuated mammary tissue inflammatory injury, suppressed the activity of myeloperoxidase, and inhibited the expression of IL-1β, IL-6, and TNF-α. In vitro experiments, the viability of MMECs was evaluated by MTT assay. qRT-PCR and ELISA results displayed that HT also reduced the pro-inflammatory cytokines expression. Molecular experiments showed that the expression of TLR2 and its downstream pathways NF-κB and MAPK were both inhibited by HT treatment. These results demonstrated that HT had a protective effect on S. aureus -induced mastitis, possibly through suppressing TLR2-mediated NF-κB and MAPK pathways.